Association between a body shape index and abdominal aortic calcification in general population: A cross-sectional study - Li, Wei; Wang, Zhenwei; Li, Min; Xie, Jing; Gong, Jing; Liu, Naifeng (Frontiers in Cardiovascular Medicine, 2023)
Background The association between a body shape index (ABSI) and abdominal aortic calcification (AAC) is still unclear, so we tried to prove the association between ABSI and AAC in the general population in this cross-sectional study. Materials and methods After excluding participants with missing data on height, weight, waist circumference (WC), and AAC, we finally selected 3,140 participants aged 40–80 years from the 2013–2014 National Health and Nutrition Examination Survey. Using multivariate logistic regression and receiver operating characteristic (ROC) curves to test the association between ABSI and AAC. Results Participants (median age: 58.0 years; 48.3% men) were divided into two groups by the optimal cutoff point of ABSI: higher ABSI (> 0.84) and lower ABSI (≤ 0.84). Participants with higher ABSI showed significantly higher proportion of AAC than those with lower ABSI (39.8 vs. 23.7%, P < 0.001). Participants with higher ABSI had an increased risk of developing AAC in crude model (ABSI as a continuous variable: OR = 2.485, 95% CI: 2.099–2.942, P < 0.001; as a categorical variable: OR = 2.132, 95% CI: 1.826–2.489, P < 0.001), and ABSI was still independently associated with AAC in all adjusted models (all P < 0.05). Further subgroup analyses showed that higher ABSI was consistently associated with AAC in subgroups with sex (male or female), age (≤ 65 or > 65 years), smoking history (yes or no), hypertension (yes or no), diabetes (yes or no), sleep disorder (yes or no), body mass index (BMI) (< 23 or ≥ 23 kg/m2), systolic blood pressure (< 140 or ≥ 140 mmHg), diastolic blood pressure (< 90 or ≥ 90 mmHg), fasting plasma glucose (< 126 or ≥ 126 mg/dL), and low-density lipoprotein cholesterol (≤ 130 or > 130 mg/dL) (P for interaction > 0.05). While in other subgroups, the association was no longer synchronized. The ROC showed that the area under the curve of ABSI was significantly higher than height, weight, BMI, WC, and waist-to-height ratio (WHtR). Conclusion Higher ABSI was closely associated with higher risk of AAC, and discriminant ability of ABSI for AAC was significantly higher than height, weight, BMI, WC, and WHtR.